Analysis on The Issue of Hijri Taqwim Development From The Perspective of Fiqh Methods and The Impact on The Unification Of The Ummah - Selmarisa Wardhani; Ibnor Azli Ibrahim (Journal of Indonesian Comparative of Syari'ah Law, 2023)
Unifying the concept of hijri taqwim is urgently needed nowadays in order to reunite the ummah. This is due to the fact that the variety of taqwim methods has posed differences in determining the beginning the new moon, as happened in the celebration of Eids Fitri this year in Indonesia. Muslims in one country and internationally are separated because of the unified taqwim system, so they often carry out various dates of prayer at different times’. This study is a qualitative study which will examine how the application of maqasid shar'iyah and selected methods summarized in the Main Fiqh Methods in hilal issues and the unification of hijri taqwim. This study will analyze some of the minor methods of the five major fiqh methods. This study found that Unifying ummah in taqwim is indeed a call written in the Qur’an and Hadith’ and Its compatibility with the fiqh methods means that it strengthens the validity, so its necessity for realization the unification of taqwim. This study also finds the Rukyah Muhaqaqah method suitable to provide a solution of the differences method in determining new moon. The method of Rukyah Muhaqaqah combines maqasid sharia as the first guideline and also technology use to realize a simple and high quality method of taqwim.